SIMPLIFIKASI MORFOLOGI ARAB (SHARF) DENGAN PENDEKATAN KONSTRUKTIVISME DAN ANALOGI - Raswan, Raswan; Abdul Wahab, Muhbib; Hakki, Syaiful (Arabi : Journal of Arabic Studies, 2022)
This study aims to develop an "Arabic morphological simplification model with a constructivism approach and the analogy of learning sharf in Fast Time." The research approach used is qualitative and quantitative types of development research (R&D). Researchers will develop an Arabic morphological model that can make neural learning successful in this fast time through surveys, interviews, documentation studies, and FGDs. It found that model was developed has succeeded in learning. Arabic education experts provide positive support to continue developing Arabic morphology models based on constructivism and analogy. Many inputs are used as references for researchers in developing the model designs that have been made. In the next stage, students as objects and public test subjects feel that neural learning becomes meaningful. Students also get a new, productive, and accessible learning model, even for those who are very 'basic,' who have always been seen as having difficulty mastering nerves.